2016
DOI: 10.1007/s40588-016-0038-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fungal Diagnostics and Therapy in Pediatric Cancer Patients in Resource-Limited Settings

Abstract: Fungal diseases are an important cause of mortality in immunocompromised hosts, and their incidence in pediatric cancer patients in low- to middle-income countries is underestimated. In this review, we present relevant, up-to-date information about the most common opportunistic and endemic fungal diseases among children with cancer, their geographic distribution, and recommended diagnostics and treatment. Efforts to improve the care of children with cancer and fungal disease must address the urgent need for su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 127 publications
1
3
0
1
Order By: Relevance
“…Platelet >×10 9 /L 21 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) 17 (15)(16)(17)(18)(19)(20)(21)(22)(23) We found that blood was the most common site of infection, which is consistent with the predominance of yeasts observed in our study. However, this finding is in contrast to reports in which lung is the most common primary site, which is expected for populations with a high risk of Aspergillus.…”
Section: Generalized 4 11supporting
confidence: 89%
See 3 more Smart Citations
“…Platelet >×10 9 /L 21 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) 17 (15)(16)(17)(18)(19)(20)(21)(22)(23) We found that blood was the most common site of infection, which is consistent with the predominance of yeasts observed in our study. However, this finding is in contrast to reports in which lung is the most common primary site, which is expected for populations with a high risk of Aspergillus.…”
Section: Generalized 4 11supporting
confidence: 89%
“…Although survival was worse among those who experienced IFI, only 1 patient died directly due to a fungal infection. It is harder to compare our IFI rates to those of low-or middleincome country centers because little data have been published Median days to engraftment (IQR) ANC > 0.5×10 9 /L 16 (13)(14)(15)(16)(17)(18)(19)(20) 17 (13)(14)(15)(16)(17)(18)(19)(20)(21) .27…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antifungal treatment of C. auris infections is further complicated by several factors, including the scale of azole resistance (e.g. 90% of C. auris isolates in the U.S. are fluconazole-resistant) (9), emergence of multidrug resistance involving two or more drug classes (19,20), and scarce availability of first-line therapy drugs, echinocandins, in resource-limited countries (21). Thus, a better understanding of the scale and molecular mechanism of AmB resistance in C. auris is urgently needed.…”
mentioning
confidence: 99%